2010
DOI: 10.1002/dvdy.22170
|View full text |Cite
|
Sign up to set email alerts
|

Mouse ZAR1‐like (XM_359149) colocalizes with mRNA processing components and its dominant‐negative mutant caused two‐cell‐stage embryonic arrest

Abstract: *Maternal effect genes and encoding proteins are necessary for nuclear reprogramming and zygotic genome activation. However, the mechanisms that mediate these functions are largely unknown. Here we identified XM_359149, a Zar1-like gene that is predominantly expressed in oocytes and zygotes, which we designated Zar1-like (Zar1l). ZAR1L-EGFP formed multiple cytoplasmic foci in late two-cell-stage embryos. Expression of the ZAR1L C-terminus induced two-cell-stage embryonic arrest, accompanied with abnormal methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 74 publications
3
39
0
Order By: Relevance
“…It could be that Zar1 and Zar2 are differentially localized within the oocyte and therefore they do not compete for the same mRNAs. For example both Zar1 and Zar2 (Zar1-like) have been found in P-body-like mRNP complexes [1, 38] suggesting that they are not homogenously distributed in the cytoplasm. Alternatively, because Zar1 and Zar2 expression peaks are at different stages of oogenesis this could indicate that they might have access to different mRNAs at these stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be that Zar1 and Zar2 are differentially localized within the oocyte and therefore they do not compete for the same mRNAs. For example both Zar1 and Zar2 (Zar1-like) have been found in P-body-like mRNP complexes [1, 38] suggesting that they are not homogenously distributed in the cytoplasm. Alternatively, because Zar1 and Zar2 expression peaks are at different stages of oogenesis this could indicate that they might have access to different mRNAs at these stages.…”
Section: Discussionmentioning
confidence: 99%
“…Zygote arrest (Zar) family proteins have been implicated in the early mitotic cleavages of the embryo, the maternal to zygote transition and epidermalization of the embryo [13]. Zar-family expression is generally confined to the oocyte and early embryo in all species tested, but in some species Zar proteins are also expressed in the testis [38].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, a comparison with mammalian mRBPomes revealed that a fraction of our zebrafish MZT mRBPome (9%) has not been previously detected in other mRNA interactomes. Indeed, it has been shown that the depletion of maternal-effect genes, Zar1 and Zar1l, causes embryonic arrest in early mouse embryos (Wu et al 2003;Hu et al 2010). Moreover, lack of maternal Piwi protein in fly embryos causes developmental defects, such as abnormal chromosome morphology and cell cycle arrest (Mani et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, most factors involved in mRNA translation (e.g., eIF4G and ribosome subunits) are normally absent from P-bodies (Kedersha et al 2005). The functions of some P-body components (e.g., ZAR1l) are unknown (Hu et al 2010). A recent cell-based siRNA screen identified proteins involved in O-linked N-acetylglucosamine (O-GlcNAc) modifications as being important for stressgranule and/or P-body formation, suggesting an important role for post-translational modifications in cytoplasmic granule formation (Ohn et al 2008).…”
Section: Introductionmentioning
confidence: 99%